The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2292550320925902
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Breast Reconstruction Information to Patients—Part 2: Women Report on Preferred Information Content

Abstract: Purpose: To determine the type of information women want to be provided in order to make an informed decision as to whether, when, and using what technique to proceed with breast reconstruction. Method: Using purposeful sampling, 19 patients who had recently undergone various breast reconstruction procedures were recruited to each participate in a 30- to 45-minute semi-structured interview. Participants shared their insights and beliefs regarding the type of breast reconstruction information they most valued p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…This study found a need for more realistic information particularly in relation to possible physical outcomes, with many respondents indicating a lack of preparedness for the look, shape and feel of their reconstructed breast. These findings are similar to research from the US, New Zealand [ 26 ], Canada [ 37 ], and the UK [ 38 ], suggesting the universality of this need. Evidence suggests that decision regret is reduced when women are satisfied with information about likely BR outcomes and can set their expectations accordingly [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…This study found a need for more realistic information particularly in relation to possible physical outcomes, with many respondents indicating a lack of preparedness for the look, shape and feel of their reconstructed breast. These findings are similar to research from the US, New Zealand [ 26 ], Canada [ 37 ], and the UK [ 38 ], suggesting the universality of this need. Evidence suggests that decision regret is reduced when women are satisfied with information about likely BR outcomes and can set their expectations accordingly [ 39 ].…”
Section: Discussionsupporting
confidence: 86%